The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1088/1126-6708/2002/08/053
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop self-dual Euler-Heisenberg Lagrangians (I): Real part and helicity amplitudes

Abstract: We show that, for both scalar and spinor QED, the two-loop Euler-Heisenberg effective Lagrangian for a constant Euclidean self-dual background has an extremely simple closed-form expression in terms of the digamma function. Moreover, the scalar and spinor QED effective Lagrangians are very similar to one another. These results are dramatic simplifications compared to the results for other backgrounds. We apply them to a calculation of the low energy limits of the two-loop massive N-photon 'all +' helicity ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 71 publications
4
117
0
Order By: Relevance
“…(2.11) in [23]). Substituting the instanton form we obtain the derivative expansion (DE) approximation (here we set ρ = 1, as before)…”
Section: Field-theoretic Derivative Expansion Approachmentioning
confidence: 96%
“…(2.11) in [23]). Substituting the instanton form we obtain the derivative expansion (DE) approximation (here we set ρ = 1, as before)…”
Section: Field-theoretic Derivative Expansion Approachmentioning
confidence: 96%
“…This function plays an important role in the quantum field theory computations in [15,16]. From the asymptotic (large x ) expansion of the digamma function [1] it follows that…”
Section: Generating Function Proof Of Miki's Identitymentioning
confidence: 99%
“…It is also well-known that many remarkable simplifications occur for such helicity amplitudes [28,29]. Recently it has been found that analogous simplifications occur in the two-loop effective Lagrangian itself [18,19,20]. At one-loop, the on-shell renormalized effective Lagrangians for a constant self-dual background can be deduced from the results of Euler and Heisenberg [22] and Schwinger [23]:…”
Section: Strong-field Limits and Beta Functions A General Argumentmentioning
confidence: 99%
“…At two-loop, the on-shell renormalized effective Lagrangians for a constant self-dual background can be expressed in closed-form [18,19,20] in terms of the digamma function,…”
Section: Strong-field Limits and Beta Functions A General Argumentmentioning
confidence: 99%
See 1 more Smart Citation